Management of Stemphylium Blight Disease Caused by Stemphylium vesicarium in Onion through Different Methodology - , Manoj Kumar Pandey; , Rudra Pratap Singh (Archives of Current Research International, 2024)
A field experiments was conducted at NHRDF, Regional Research Station, Nashik in two consecutive years during rabi 2022-23 and 2023-24 on onion for the management of stemphylium blight disease through different methodology like alteration in transplanting dates, chemical and bio-pesticides management as well as screening of stemphylium tolerant variety. In case of alteration in transplanting dates that the lowest intensity (9.83%) of stemphylium blight and highest yield (391.83 q/ha) was recorded on 3rd week of December. In case of chemical fungicides with bio pesticides the lowest stemphylium blight disease intensity (7.27%) as well as highest yield (399.17 q/ha) was recorded in treatment T4 (Tebuconazole50% + Trifloxystrobin 25% WG @ 0.15% at 45, 60 and 75 DAT while, in case of varietal screening the lowest intensity (10.93%) of stemphylium blight as well as highest gross yield (397.00 q/ha) with marketable (383.83 q/ha) was recorded in variety NHRDF Red-4.